EKSPLORASI DAN IDENTIFIKASI CENDAWAN ANTAGONIS TERHADAP JAMUR AKAR PUTIH (Rigidoporus lignosus) PADA TANAMAN PALA (Myristica fragrans Houtt) - Nana Ariska; Lola Adres Yanti; Chairudin Chairudin (Jurnal Agrotek Lestari, 2020)
Nutmeg (Myristica fragrans Houtt) is a multipurpose plantation commodity crop that almost all parts of the plant have strategic economic value to be cultivated. In Indonesia there are the largest nutmeg commodity centers, including the Maluku islands, North Sulawesi and Aceh. The biggest problem with nutmeg plants is the attack of pests and diseases. One of the most severe diseases in nutmeg is white root mushroom (Rigidoporus lignosus). This study aims to 1) determine the fungus of white root fungus antagonists (Rigodoporus lignosus) from the Aceh nutmeg rhizosphere (Myristica fragrans Houtt), 2) identify the content of antibiotic fungus JAP antagonist compounds in Aceh nutmeg plants. The study was conducted by taking soil samples from nutmeg plants at three nutmeg plantations in South Aceh. The antagonist fungus isolation activity uses a dilution method. Isolation of JAP from infected roots using direct planting method. Furthermore, it is identified macroscopically and microscopically. The antagonist test was carried out using the dual culture method with RAL. From the rhizosphere in the nutmeg area, 5 candidate antagonist isolates were obtained, having high in vitro antagonism ability to the pathogen R. lignosus. Identification results showed that isolates 1, 2 and 3 were Trichoderma spp, and isolates 4 and 5 were Gliocladium virens. Keywords: In vitro, the content of antibiotic compounds, Aceh nutmeg, Rigidoporus lignosus, antagonistic test